A Cartel Analysis of the German Labor Institutions and Its Implications for Labor Market Reforms - Justus Haucap; Uwe Pauly; Christian Wey (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
In this paper we apply standard cartel theory to identify the major institutional stabilizers of Germany?s area tariff system of collective bargaining between a single industry union and the industry?s employers association. Our cartel analysis allows us to demonstrate that recent labor policy reforms that intend to make labor markets more ?flexible? further serve to stabilize the labor cartel while other pro-competitive proposals have failed. We argue that the pro-competitive recommendations failed exactly because of their destabilizing effects on insiders? incentives to stay in the labor cartel. We propose regulatory measures for injecting competition into Germany?s labor markets that focus on the creation of new options for firms and workers outside the existing area tariff system; in particular, by liberalizing existing barriers for the establishment of a fully tariff-enabled union. Such an endeavor must go hand in hand with the institutionalization of a competition policy framework for labor market disputes as any destabilizing policy inevitably provokes counter measures of the incumbent labor cartel so as to protect their dominance vis-?-vis outsider competition.
Keywords: K31; J52; L12; 330; Union; Collective Bargaining; Cartel Stability; Labor Market Reforms; Tarifpolitik; Lohnverhandlungen; Kartell; Insider-Outsider-Modell; Arbeitsmarktflexibilisierung; Deutschland